A Review: Development of Photocatalyst Materials and Its Performance for Humic Acid Removal in Peatwater - Siti Unvaresi Misonia Beladona; Riandy Putra; Rokiy Alfanaar; Miranti Maya Sylvani; Elda Alyatikah; Riaa Safitri; Indri Susanti; Rendy Muhamad Iqbal (Center for Development of Science, Technology and Peatland Innovation (PPIIG), University of Palangka Raya, 2022)
Peat is a wetland region in Indonesia with a very high water storage capacity. However, the amount of humic compounds obtained from the accumulation of organic substances in peat makes the water unable to be used for daily purposes. Peat water treatment with several methods has been carried out, such as coagulation, electrocoagulation, flocculation, and filtration. However, the result of clumping or filtering in such a way raises new environmental problems. One method which effective and efficient used in peat water treatment is photocatalytic. Several materials based-semiconductor was developed as a photocatalyst, another modification of photocatalyst is combining the adsorbent as a porous supporting photocatalyst which can improve its performance.